A chemoreceptor from Pseudomonas putida forms active signalling complexes in Escherichia coli - Herrera Seitz, M. Karina; Soto, Débora; Studdert, Claudia A. (Microbiology (Society for General Microbiology), 2012)
Chemoreceptors sense environmental stimuli and transmit the information to the flagellar motors via a histidine kinase that controls the phosphorylation level of the effector protein CheY. The cytoplasmic domain of chemoreceptors consists of a long α-helical hairpin that forms, in the dimer, a coiled-coil four-helix bundle. Even though the sequence and general structure of the cytoplasmic domain are strongly conserved within Eubacteria and Archaea, the total length of the α-helical hairpin is variable and defines seven classes of chemoreceptors. In this work we assessed the functional properties of a Pseudomonas receptor when assembled in signalling complexes with Escherichia coli proteins. Our results show that the foreign receptor does not confer fully chemotactic abilities upon E. coli cells, but is able to form active ternary complexes that respond to the specific stimuli by modulating the activity of the associated kinase. The observed responses are subject to adaptation, depending on the presence of the methylation enzymes CheR and/or CheB. The ability of foreign receptors to signal through signalling complexes with non-cognate proteins would allow the use of the well-studied E. coli system to reveal the detection specificity of uncharacterized chemoreceptors from other micro-organisms.